(untitled) (Marketing Journal, 2026)
Abstract The purpose of this paper is to evaluate profitability and provide indicators on how it can be improved: using Etsy as a case study. Considering that Etsy has stable revenue growth, successful operational structure and sustainable business model, it can provide information on enhancing profitability. It is believed that profit is the main driver of a business, as it is necessary for a company to survive in the long-run. This article illustrates the financial status of Etsy, using horizontal and vertical methods and profitability ratios which include the factors effecting company’s profit. Furthermore, it examines the efficiency of a company’s activity, potential risks, competitiveness and continuity. Keywords: Profit, financial ratios, Etsy, net income, operational costs, business performance, revenue, profitability of assets, profitability of equity.